Open University (UT) is the first university used distance learning systems. Therefore, some important aspects that must be possessed by students in this learning system is the desire and ability to learn independently, and then motivation to progress and develop. Distance teaching and learning process is basically addressed to the readiness and motivation of students to study independently. This study uses two-factor theory of motivation namely intrinsic and extrinsic motivation. Therefore, in - Devi Ayuni; Sri Hartoyo; Sukiswo Dirdjosuparto (Forum Pasca Sarjana, 2011)
Open University (UT) is the first university used distance learning systems. Therefore, some important aspects that must be possessed by students in this learning system is the desire and ability to learn independently, and then motivation to progress and develop. Distance teaching and learning process is basically addressed to the readiness and motivation of students to study independently. This study uses two-factor theory of motivation namely intrinsic and extrinsic motivation. Therefore, in facing the problem of student motivation, UT needs to provide excellent service to support and motivate the student. To achieve an excellent service UT must have certain skills in human resources. Based on the existing problems, the purpose of this study were to analyze the affect of intrinsic motivation, extrinsic motivation, and excellent service toward the satisfaction of a student graduate at Management Study Program, Economic Faculty of Open University. This study used crosstabs and multiple regression analysis.  From the analysis showed that significantly the affect between intrinsic motivation, extrinsic motivation, excellent service, and dummy variable of graduation period, and education level.   Key words:  intrinsic motivation, extrinsic motivation, excellent service, student graduate satisfaction